To expand the expression \((4x^2 - x + 9)(x^2 + 2x + 1)\), we will follow a similar process as in the example.
Step 1: Distribute each term in the first polynomial to each term in the second polynomial.
-
Distributing \(4x^2\):
- \(4x^2 \cdot x^2 = 4x^4\)
- \(4x^2 \cdot 2x = 8x^3\)
- \(4x^2 \cdot 1 = 4x^2\)
-
Distributing \(-x\):
- \(-x \cdot x^2 = -x^3\)
- \(-x \cdot 2x = -2x^2\)
- \(-x \cdot 1 = -x\)
-
Distributing \(9\):
- \(9 \cdot x^2 = 9x^2\)
- \(9 \cdot 2x = 18x\)
- \(9 \cdot 1 = 9\)
Step 2: Combine all these results together: \[ 4x^4 + 8x^3 + 4x^2 - x^3 - 2x^2 - x + 9x^2 + 18x + 9 \]
Step 3: Gather all like terms:
- \(4x^4\) (only one term)
- The \(x^3\) terms: \(8x^3 - x^3 = 7x^3\)
- The \(x^2\) terms: \(4x^2 - 2x^2 + 9x^2 = 11x^2\)
- The \(x\) terms: \(-x + 18x = 17x\)
- The constant term: \(9\) (only one term)
Final Step: Write the polynomial in standard form: \[ 4x^4 + 7x^3 + 11x^2 + 17x + 9 \]
Thus, the expanded form of \((4x^2 - x + 9)(x^2 + 2x + 1)\) in standard form is: \[ \boxed{4x^4 + 7x^3 + 11x^2 + 17x + 9} \]